Dental Facilities During the New Corona Outbreak: A SWOT Analysis - Gaffar B; Alhumaid J; Alhareky M; Alonaizan F; Almas K (Dove Medical Press, 2020)
Balgis Gaffar,1 Jehan Alhumaid,1 Muhanad Alhareky,1 Faisal Alonaizan,2 Khalid Almas1 1Preventive Dental Sciences Department, College of Dentistry, Imam Abdulrahman Bin Faisal University, Dammam, Saudi Arabia; 2Restorative Dental Sciences Department, College of Dentistry, Imam Abdulrahman Bin Faisal University, Dammam,Saudi ArabiaCorrespondence: Balgis Gaffar Tel +966 542269941Email bgosman@iau.edu.saAbstract: Recently, there have been many global outbreaks of diseases. The latest is the coronavirus disease of 2019 (COVID-19) pandemic. The virus has spread worldwide and is transmitted mainly through droplets or by touching contaminated surfaces. Globally, healthcare systems are challenged due to a lack of workplace safety and professional obligations in addition to the rapid spread of the virus. Dental facilities are at greater risk due to the nature of dental care. The aim of this review study was to provide a situational analysis within dental facilities during the new COVID-19 outbreak. Published papers concerning dental facilities and COVID-19 were retrieved from PubMed, search engines, and organizational websites. All data were reviewed, arranged into themes, and then categorized either as strengths or weaknesses with respect to addressing the COVID-19 pandemic in dental facilities, and accordingly, threats and possible opportunities to the handling of the pandemic were identified. Preparedness of dental facilities during the current pandemic is a weakness that needs to be addressed promptly. Shortage of dental care providers, cyber security, economic losses, and ethical challenges are possible threats due to the current outbreak. Coordination and prompt communication among all healthcare providers during such outbreaks is a strength that needs to be supported. This strengths, weaknesses, opportunities, and threats (SWOT) analysis can be a useful tool for guiding decision-making as it is crucial during the current pandemic to work on weaknesses, avoid threats, and utilize all future opportunities.Keywords: COVID-19, dental clinics, SWOT, preparedness, challenges